SPIRITUALITAS DAN HAPPINESS PADA REMAJA AKHIR SERTA IMPLIKASINYA DALAM LAYANAN BIMBINGAN DAN KONSELING - Wahidin Subari (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
Adolescents are often perceived by parents and teachers as future rebels, risky, materialistic, emotional, depressed, stubborn and rude. Furthermore, adolescents identical to storm and stress are characterized by high volatility in the face of the problem itself. Teenagers who are close to the religious life will be easier happier than those far from the religious life. This study aimed to explore the correlation of spirituality and happiness in the late teens to the 2nd generation students of Muhammadiyah University Tasikmalaya. This study uses bivariate correlational. Data retrieval through purposive sampling techniques, the student of the 2nd course of study Guidance and Counseling University of Muhammadiyah Tasikmalaya. The respondents of this study amounted to 53 people, consisting of 38 women and 15 men. The average age of respondents was 19.91 years, SD: 1.097. Spirituality has a significant correlation with happiness in the late teens students of Muhammadiyah University Tasikmalaya. The magnitude of the correlation is 0.673 (+ number), the higher the spirituality of the higher happiness in adolescents. Spirituality has a role amounted to 45.2% against happiness.